SI/IT STRATEGIC PLANNING USING WARD AND PEPPARD METHODS (CASE STUDY: PT. XY) - Wijanarko, Rediva Kezia (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2022)
The role of information systems in the company is an important part to assist in business processes. However, there are still obstacles in the company's business processes that are not appropriate with the vision and mission as well as the goals of the company. So, good and appropriate IS/IT strategic planning is needed to be able to help companies compete. The purpose of this research is to analyze the strategic planning of the business information system of PT. XY so that it is expected to solve the problem. This study uses a qualitative method conducted by conducting interviews with one of the employees and literature studies which are then analyzed using the Ward and Peppard method which includes Value Chain Activity analysis, Five Competitive Forces analysis, SWOT analysis, Application Portfolio using McFarlan Strategic Grid and proposal analysis information systems. The final result of this research is a portfolio of information system applications such as a Website-based Inventory Management System. In addition, there is an implementation plan for the proposed information system which is expected to help business processes become more efficient and effective